Argentine government policies: impacts on the beef sector - Gustavo Rossini; Rodrigo García Arancibia; Edith Depetris Guiguet (Agricultural and Food Economics, 2017)
Beef is a staple food for Argentine consumers, and although the country has been a major exporter, the highest proportion of beef production is consumed in the domestic market. With rising inflation rates in the last 5 years, and given the beef prices' strong weight on the composition of the Consumer Price Index, the Argentine government began taking measures to control it. They initially forced price agreements with members of the marketing and production chain and ended up with a total ban on exports. The results were not as expected and caused serious distortions at different levels of the beef chain. This study aimed to determine whether the impact on some economic and production variables would have been different without such intervention. A VAR model was estimated in order to compare the observed behavior with intervention measures and estimated predictions with a theoretically free market.
Keywords: 330; Argentine beef exports; VAR model; Policy impacts